Randomized trial of ticagrelor vs. aspirin in patients after coronary artery bypass grafting: the TiCAB trial. (30th May 2019) - Schunkert, Heribert; Boening, Andreas; von Scheidt, Moritz; Lanig, Clarissa; Gusmini, Friederike; de Waha, Antoinette; Kuna, Constantin; Fach, Andreas; Grothusen, Christina; Oberhoffer, Martin; Knosalla, Christoph; Walther, Thomas; et al.
Abstract: Aims: The antiplatelet treatment strategy providing optimal balance between thrombotic and bleeding risks in patients undergoing coronary artery bypass grafting (CABG) is unclear. We prospectively compared the efficacy of ticagrelor and aspirin after CABG. Methods and results: We randomly assigned in double-blind fashion patients scheduled for CABG to either ticagrelor 90 mg twice daily or 100 mg aspirin (1:1) once daily. The primary outcome was the composite of cardiovascular death, myocardial infarction (MI), repeat revascularization, and stroke 12 months after CABG. The main safety endpoint was based on the Bleeding Academic Research Consortium classification, defined as BARC ≥4 for periprocedural and hospital stay-related bleedings and BARC ≥3 for post-discharge bleedings. The study was prematurely halted after recruitment of 1859 out of 3850 planned patients. Twelve months after CABG, the primary endpoint occurred in 86 out of 931 patients (9.7%) in the ticagrelor group and in 73 out of 928 patients (8.2%) in the aspirin group [hazard ratio 1.19; 95% confidence interval (CI) 0.87–1.62; P  = 0.28]. All-cause mortality (ticagrelor 2.5% vs. aspirin 2.6%, hazard ratio 0.96, CI 0.53–1.72; P  = 0.89), cardiovascular death (ticagrelor 1.2% vs. aspirin 1.4%, hazard ratio 0.85, CI 0.38–1.89; P  = 0.68), MI (ticagrelor 2.1% vs. aspirin 3.4%, hazard ratio 0.63, CI 0.36–1.12, P  = 0.12), and stroke (ticagrelor 3.1% vs. 2.6%, hazard ratio 1.21, CI 0.70–2.08; P  = 0.49), showed no significant difference between the ticagrelor and aspirin group. The main safety endpoint was also not significantly different (ticagrelor 3.7% vs. aspirin 3.2%, hazard ratio 1.17, CI 0.71–1.92; P  = 0.53). Conclusion: In this prematurely terminated and thus underpowered randomized trial of ticagrelor vs. aspirin in patients after CABG no significant differences in major cardiovascular events or major bleeding could be demonstrated. ClinicalTrials.gov Identifier: NCT01755520.